Factors of pregnant women’s interest in utilizing the provider-initiated testing and counseling (PITC) services - Novika, Almira Gitta; Maydianasari, Lenna (Jurnal Kesehatan Ibu dan Anak, 2019)
HIV infection has become one of the complications of pregnancy that often occurs. Efforts to minimize this risk are HIV testing and counseling services on the initiative of health workers or Provider Initiated Testing and Counseling (PITC). This study analyzes the determinant factors of pregnant women's interest in utilizing PITC services. This research used a quantitative approach combined with a qualitative approach (Mixed Method). The research conducted in Depok II Public Health Center (PHC), Sleman Regency. Data analysis techniques were using Chi-Square, multiple logistic regression, and content analysis. This study shows that there is no correlation between the level of knowledge (p=0.214), stigma and discrimination against HIV/AIDS (p=0.536), the support of husband (p=0.092), and the support of health workers (p=0.161) with the interest of pregnant women in utilizing PITC services. There is a relationship between attitude (p=0.000), needs (p=0.002), and belief (p=0.004) with the interest of pregnant women in utilizing PITC services. The result of multiple logistic tests stated that attitude was the determines (p= 0.000, 95% CI= 0.036-0.393). The results of the quantitative data analysis showed that the majority of husband support was in a good category (56.6, and the majority of health workforce support was in a good category (77.1%). The attitude was the most determining factor of the interest of pregnant women in utilizing PITC services.